(untitled) (Filološke studije, 2019)
Spatiatility in literature can be understood and conceived from many aspects. In this work I will try to represent the space as one of possible approaches to study of intercultured literature. Intercultured literature, whose name includes certain spatiatility, is suitable for researching of “intercultured“ authors and literatures where the space of their movements would be researched. As paradigm to this work two novels by Irfan Horozović will serve me and they are Pisaći stroj ručne izrade (1983) and Kalfa (1988). Those two novels with their inception (written in one town/country, and printed in other) include implicitly particular spatiatility and precisely because inception in some other, enable reading off the one. We will see how is so-called hybridity of this author read off with the help of towns (Banja Luka and Zagreb), and the house (attic and cellar). In his view, the town is the place of recognition of identity, and the house is the place of day dreaming and returning to past, native, maternally.